Retrospective analysis of probationers: sociodemographic characteristics, individual and familial history of addiction and crime, and treatment outcomes - Altıntoprak, A.Ender; Akgür, Serap A.; Kitapçıoğlu, Gül; Yüncü, Zeki; Coşkunol, Hakan (Journal of Dependence, 2014)
Objective: The first Turkish drug treatment court was started in 2006. In this study, the files of the probationers who referred to our addiction center for a one year period were evaluated according to their sociodemographic characteristics, the history of personal and familial alcohol/drug use, the characteristics of personal substance related crimes and non-substance related crimes and familial criminal history. Toxicological analyses during the treatment period and treatment outcomes were evaluated also.Method: The research is a decriptive and cross sectional study. Overall, one hundred and twenty nine files of probationers, who did not have comorbid mental disease, were evaluated. Data was analyzed by SPSS 15.0 statistics program.Results: The 98.2% of subjects were male (n=128), 0.8% (n=1) of the sample was female. The mean age of the subjects was 33.1 ± 11.6 (18-69). Results of the toxicological analysis during the probation period showed that in 46.5% of the subjects no substance was detected; in 38.8% of the subjects marijuana; in 1.5 % of the subjects cocaine; in 1.5% of the subjects amphetamine, in 0.8% of the subjects opiate and in 0.8% of the subjects multisubstance was detected. The analysis of treatment outcomes showed that 46,5% of subjects had positive final reports.Conclusion: This is the first study that evaluated the sociodemographic, personal and familial alcohol/substance use and criminal histories of the probationers who refered to mandatory treatment for substance use in Turkey. The growing knowledgeon thisissue may contribute to the development of the most proper treatment and prevention programsforthis population.
Keywords: Illicit drug; toxicological analysis; crime; probation